Self-Transformation of Students in The Six Plus Six Multi Talenta Program through Learning Experiences in the Tourism and Hospitality Industry - Andri Wibowo; Arina Luthfini Lubis; Zahara Fatimah; Naya Sabrina (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2026)
This study aims to explore students’ self-transformation through learning experiences in the Six Plus Six Multi Talenta Program within the tourism and hospitality industry. A qualitative approach using Narrative Inquiry was employed to understand how students interpret their learning experiences during six months of academic study at Batam Tourism Polytechnic and six months of On-the-Job Training (OJT) in the hospitality industry. Data were collected through in-depth interviews, observations, and documentation involving students from the Room Division Management program. The findings reveal that learning experiences gained through the integration of campus-based education and industry-based training contribute not only to the development of technical and soft skills but also to significant changes in students’ mindsets, work attitudes, and professional identity. Students perceived the program as an opportunity to understand the realities of the workplace, develop adaptability, strengthen discipline and responsibility, and prepare for future careers in the tourism and hospitality sector. The study further demonstrates that self-transformation occurs through a continuous process of learning, reflection, adaptation, and professional identity formation. These findings highlight the importance of experiential and work-based learning in fostering competent, adaptable, and industry-ready human resources for the tourism and hospitality sector.